중국 소비행태와 한국 농식품 수출마케팅 전략 - 손창수 (한국농촌경제연구원, 2013)
After starting the negotiation for FTA between Korea and China, Korean efforts to promote exportation of Korean agro-food for Chinese consumers have been intensified. However, few papers tried to analyze Chinese consumers’ behavior about Korean food in Chinese market, which is the initial point to discuss about export promotion of Korean agro-food. The purpose of this paper is to analyze consumers' behavior about Korean food in China. This research conducted a survey in 4 major cities (Beijing, Shanghai, Guangzhou, and Tsingtao) and presented suitable market segmentation and target market for Korean agro-food in Chinese market through a factor analysis and a cluster analysis. The study results present the possibility of increasing consumers’ preference in Chinese market. Korean agro-food is preferred by the consumer group with higher income and education level. Consumers in Beijing, in particular, might be the first target market for Korean agro-food.